HUBUNGAN PENGETAHUAN LANSIA TENTANG OSTEOPOROSIS DENGAN UPAYA PENCEGAHAN RESIKO JATUH DI RW 01 DESA KARANG REJO KECAMATAN YOSOWILANGUN KABUPATEN LUMAJANG - Dwi Ana, Karisma; Retnaning Gumilar, Cindrawati; Fatmawati, Istiadah (PRIMA WIYATA HEALTH, 2022)
Getting old is a natural process. In old age, physical or biological conditions, psychological conditions, and social conditions will decline. One of the health issues that elderly people need to pay attention to is osteoporosis. A common disease of the elderly with osteoporosis is falls. The aim of the study was to investigate the relationship between older people's knowledge of osteoporosis and fall prevention efforts in Karangrejo Village, RW 01, Yosovilangun District, Lumajang Regency. The research design used was a correlational design with a cross-sectional approach. Some of the elderly in Karangrejo Village, RW 01, Yosowilangun District, used a non-probability technique called Purposive sampling. The measuring instrument used is an observation sheet that is analyzed using the Spearman Rho test. The significance level for the test is 5%. The results of this study indicate that 10 respondents (21.7%) have good knowledge and fall risk prevention efforts in the category 6 respondents (13.3%). Meanwhile, we obtained the value for the Spearman-Rho correlation test. (2-side) or the value 0.001 (because the value < 0.05) then H0 is rejected and H1 is accepted.There is a relationship between knowledge of the elderly about osteoporosis and prevention of fall risk in Karangrejo village, RW 01, Yosowilangun district, Lumajang district, the better the elderly's knowledge about osteoporosis, the better the fall risk prevention efforts.